Homeostasis - Sevigny, Charles (Henry Stewart Talks, 2022)
Physiology, Homeostasis, Negative feedback loop, Positive feedback, Diffusion, Cell membrane, Osmolarity and tonicity, Osmotic equilibrium, Fick’s law, Hypotonic solutions